2011
DOI: 10.1108/17537981111190051
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of process and competitive factors of entrepreneurship in digital space

Abstract: Purpose -The purpose of this paper is to explore the process and competitive factors of entrepreneurship in digital space in Iran. Design/methodology/approach -In the last decades, the development and advancement of information and communication technologies (ICTs) and the business innovations related to them have defined a new economy which is known as "digital economy". Establishing and running businesses in this digital space means carrying out a kind of electronic commerce by exploiting the internet and ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 20 publications
0
32
0
1
Order By: Relevance
“…The advancement of information and communications technology in society has given rise to more digital businesses (Cohen et al, 2000). Hafezieh et al (2011) suggested that digital entrepreneurship enables the carrying out of a business using electronic commerce, the internet and other social media devices. More businesses are using digital entrepreneurship as a way to compete in the global economy (Gerguri-Rashiti et al, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The advancement of information and communications technology in society has given rise to more digital businesses (Cohen et al, 2000). Hafezieh et al (2011) suggested that digital entrepreneurship enables the carrying out of a business using electronic commerce, the internet and other social media devices. More businesses are using digital entrepreneurship as a way to compete in the global economy (Gerguri-Rashiti et al, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…This leads to conclusion that voluntary nature of consumers may also determine a non-deceptive nature of digital shadow economy. What concerns the channels of digital shadow economy, the analysis of the scientific literature has revealed that acting in digital space means exploitation of the remote space such as online shops, online service provision websites and social networks (Hafezieh et al 2011;Levi, Williams 2013;Amasiatu, Shah 2014), e-advert and e-auction sites (Vlachos et al 2011;Dion 2011;Smith 2015), cyber gambling and e-game portals (Vlachos et al 2011;Smith 2015), online broadcasts (Dion 2011;Dobson et al 2015), bitcoins and other cryptographic currencies (Haines, Johnstone 1999;Holz et al 2012;Zorz 2015). With reference to Smith (2015), the channels of digital underground economy may include Internet access, computer hard drive space, financial resources, intellectual capital and other data or bandwidth.…”
Section: Concepts Features and Channels Of Digital Shadow Economy: Tmentioning
confidence: 99%
“…What concerns the channels of digital shadow consumption, the analysis of the scientific literature has disclosed that engagement of particular channels for acquisition of goods/ services online means exploitation of the remote spaces such as online shops, online service provision websites, social networks (Hafezieh et al 2011;Levi, Williams 2013;Amasiatu, Shah 2014), e-advert and e-auction sites (Vlachos et al 2011;Dion 2011;Smith 2015). Hence, the channels mentioned above will be proposed for consumers' assessment in the empirical part of the research.…”
Section: The Determinants and Channels Of Digital Shadow Consumption:mentioning
confidence: 99%